2011
DOI: 10.1136/sextrans-2011-050099
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 2 serological testing and psychosocial harm: a systematic review

Abstract: HSV-2 diagnosis by type-specific serological testing did not result in long-term psychosocial harm in most persons without an identified history of genital herpes. Concerns about sustained emotional impact should not deter clinicians from offering HSV-2 serological testing to appropriate patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 44 publications
0
13
0
2
Order By: Relevance
“…A review examined studies that measured the short and long-term psychosocial effects resulting from serological diagnosis of HSV-2 in persons without recognized symptoms of genital herpes infection [58]. Overall HSV-2 serological testing did not result in long-term psychosocial harm in most people.…”
Section: Introductionmentioning
confidence: 99%
“…A review examined studies that measured the short and long-term psychosocial effects resulting from serological diagnosis of HSV-2 in persons without recognized symptoms of genital herpes infection [58]. Overall HSV-2 serological testing did not result in long-term psychosocial harm in most people.…”
Section: Introductionmentioning
confidence: 99%
“…Only 2 of the 8 found a lasting, negative impact of an HSV diagnosis and the majority concluded that concern about psychological impact should not deter HSV screening programs. 7 Despite these reassuring findings, caution is warranted when screening adolescents and young adults for HSV. Psychosexual development is a key task of adolescence and young adulthood.…”
Section: Are the Costs And Risks Of Screening Less Than The Benefits?mentioning
confidence: 96%
“…[24] Nevertheless, a recent review of the extant literature concluded that HSV-2 diagnosis by type-specific serological testing did not result in long-term psychosocial harm in most persons without an identified history of genital herpes. [25] That review, however, was limited to studies with adults from developed countries. Moreover, conclusions were aimed at clinicians, who were advised to offer HSV-2 testing selectively to “appropriate” patients.…”
Section: Introductionmentioning
confidence: 99%